1963
DOI: 10.1071/bi9630350
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Proteins of Developing Wheat Endosperm: Fractionation by Ion-Exchange Chromatography

Abstract: Protein fractions were extracted from endosperm isolated from developing grains of Gabo, Insignia, and Dural varieties of wheat. The changes in total nitrogen and in the distribution of nitrogen in the various extracts were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1963
1963
1971
1971

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…have shown that the fraction extracted by pyrophosphate buffer contains a relative predominance of proteins which are fast moving on electrophoresis in starch gel, whereas the proteins subsequently extracted by acetic acid have a relative predominance of slow-moving components. The relative constancy of the amino acid composition of the proteins extracted with acetic acid is consistent with the view that these proteins form a considerable proportion of the storage proteins of wheat endosperm Graham, Morton, and Simmonds 1963). Table 4 shows that the amount of amino acid residues in each of the protein fractions increase considerably during development, the distribution between the proteins extracted by pyrophosphate, acetic acid, and sodium hydroxide reflecting the distribution of total protein nitrogen bet"i'een these fractions (see also Graham, Morton, and Simmonds 1963;.…”
Section: (B) Ohanges In Amino Acids Of Endosperm Dnring Developmentsupporting
confidence: 63%
See 1 more Smart Citation
“…have shown that the fraction extracted by pyrophosphate buffer contains a relative predominance of proteins which are fast moving on electrophoresis in starch gel, whereas the proteins subsequently extracted by acetic acid have a relative predominance of slow-moving components. The relative constancy of the amino acid composition of the proteins extracted with acetic acid is consistent with the view that these proteins form a considerable proportion of the storage proteins of wheat endosperm Graham, Morton, and Simmonds 1963). Table 4 shows that the amount of amino acid residues in each of the protein fractions increase considerably during development, the distribution between the proteins extracted by pyrophosphate, acetic acid, and sodium hydroxide reflecting the distribution of total protein nitrogen bet"i'een these fractions (see also Graham, Morton, and Simmonds 1963;.…”
Section: (B) Ohanges In Amino Acids Of Endosperm Dnring Developmentsupporting
confidence: 63%
“…INTRODUCTION During the development of wheat endosperm, there is rapid synthesis of proteins, which may be fractionated by successive extraction with sodium pyrophosphate, acetic acid, and sodium hydroxide (Graham, Morton, and Simmonds 1963). have described the changes in the major nitrogenous constituents during grain development.…”
mentioning
confidence: 99%
“…Between day 12 and day 20, a considerable amount of starch fills the enlarging endosperm cells; Plate 1, Figures 2 and 3, shows both large ellipsoidal grains, which are formed first, and smaller spheroidal grains which are formed later during development. During this latter period especially, protein synthesis in endosperm is rapid (Graham, Morton, and Simmonds 1963;Jennings and Morton 1963a). However, neither by fluorescencenor by phase-contrast microscopy of fresh tissue, with or without staining with methylene blue, could the localization of protein in the cells be established.…”
Section: (A) Generalmentioning
confidence: 99%
“…Between day 14 and maturity, storage proteins (soluble in acetic acid or in sodium hydroxide) increase considerably as compared with buffer-soluble proteins Graham, Morton, and Simmonds 1963). To follow the related changes in intracellular structure during this period, comparable pieces of endosperm tissue Were fixed in osmium tetroxide or in potassium permanganate; electron micrographs were made of suitable sections after both types of flxation.…”
Section: (0) Accumulation Of Protein and Of Electron-dewe Bodies Durimentioning
confidence: 99%
See 1 more Smart Citation